Kajian Kesesuaian Wisata Dan Daya Dukung Kawasan Wisata Ancol Arung Jeram Kecamatan Sipispis Kabupaten Serdang Bedagai Sumatera UtaraKajian Kesesuaian Wisata Dan Daya Dukung Kawasan Wisata Ancol Arung Jeram Kecamatan Sipispis Kabupaten Serdang Bedagai Sum - Siti Hamidah; Zulham Apandy Harahap (AQUACOASTMARINE, 2018)
Ancol Arung Jeram is a tourism place that used medium of rafting recreation and natural bathing which often visited by local tourist. This research aims to analyze the suitability of level tourism and carrying capacity of the area based on the physical condition of the Ancol Arung Jeram as object of tourism place and assess visitors perceptions of activities of tourist in Ancol Arung Jeram. The research was done on last of February until March 2018. Ancol Arung Jeram was used by visitors to do activities of natural bathing and rafting of course the activities will be supported by pontential in the region.The carrying capacity of the tourism of Ancol Arung Jeram in rafting category is 425 people/day and natural bathing category is 772 people/day. Tourism suitability index for rafting category is included in S1 (Very Suitable) and the natural bathing category is (Very Suitable).Keywords: Ancol Arung Jeram, regional carrying capacity, tourist suitability index, bath ,rafting ,ecotourism.